Interactions between invading benthivorous fish and native whitefish in subarctic lakes. (3rd March 2013) - Hayden, Brian; Holopainen, Tiina; Amundsen, Per‐Arne; Eloranta, Antti P.; Knudsen, Rune; Præbel, Kim; Kahilainen, Kimmo K.
Summary: Many species are expanding their distribution towards higher latitudes and altitudes in response to climate change. These range shifts are expected to change fish community structure and alter food‐web dynamics in subarctic lakes. However, the impacts of invading species on native fish and invertebrate prey communities remain understudied. The trophic ecology of invasive species determines the likelihood of direct resource competition with native taxa. In Northern Europe, perch ( Perca fluviatilis ), a trophic generalist, and ruffe ( Gymnocephalus cernuus ), a benthic specialist, are expanding their distribution ranges northwards, colonising lakes inhabited by a native generalist, whitefish ( Coregonus lavaretus ). We predicted that increased fish diversity and density would deplete the invertebrate community and increase resource competition between native and invasive species. To assess the degree of resource competition between native and invasive species, we compared (i) fish and invertebrate community structure; (ii) diet and stable carbon and nitrogen ratios of whitefish, ruffe and perch and (iii) growth, condition and relative population size of whitefish in two non‐invaded lakes with two lakes containing one and two lakes containing both invasive species. Each lake was sampled on a single occasion between August and September. Benthic macroinvertebrate density and community structure were unaffected by increased consumer diversity, while top‐down control of pelagic zooplankton density and size was evident in lakes with increased fish diversity. Differences in diet and stable isotope ratios were evident between all whitefish populations, although these were not directly related to the presence of invasive species. Specialised adaptations of invasive species may confer a competitive advantage in invaded lakes; ruffe dominated the profundal niche, while perch displayed an ontogenetic shift to piscivory, reducing niche overlap with native whitefish. Growth rate and population density of whitefish were largely independent of fish community structure and were governed by local variations in lake productivity. However, there was a sign of lowered condition of whitefish in invaded systems. Shallow and more productive lakes with higher food availability supported populations of native and invasive species. Our findings indicate that trophic specialisations of invasive species play a key role in determining their impacts on the systems they invade. This study focussed on early stages of invasion, and the outcome of species interactions may change following the establishment of new species. In addition, these impacts will not be uniform across the invaded landscape as lake‐specific variations in morphometry and resource availability will alter the competitive balance between native and invasive species.